Short communication. Single nucleotide polymorphisms in the ovine CSN1S2 gene for alphaS2–casein - Padilla, J. A.; Corral, J. M.; Quesada, A.; Izuierdo, M.; Parejo, J. C.; Martínez-Trancón, M. E. (Spanish Journal of Agricultural Research, 2013)
This work describes eighteen SNPs (9 transitions and 9 transversions) found in the sequence spanning from exon 7 to 11 of the CSN1S2 ovine gene, thirteen located at the introns 7 (5 SNPs), 8 (2 SNPs), 9 (1 SNP), and 10 (5 SNPs), and five at the exons 10 (4 SNPs) and 11 (1 SNP). The allele frequencies of the SNPs have been obtained from seventeen animals of Merino breed. Among intronic polymorphisms, the two adjacent SNPs g.[435C>A; 436T>G] are located at the pyrimidine rich box near the 3’ splice acceptor site of intron 10, which could potentially affect mRNA processing. Analysis of the deduced amino acid sequences from exons 10 and 11 showed that polymorphisms ex10-g.153G>T and ex10-g. 155C>T, which affect the same codon, and ex11-g. 504A>G, are non-synonymous substitutions producing the amino acid changes Asp75 to Tyr75 and Ile105 to Val105, respectively, giving rise to the A and B alleles previously found by direct sequencing of the mature protein. For these SNPs only six of the eight possible combinations were detected, GCA being the most frequent haplotype (0.323), corresponding to Asp75 – Ile105 in the mature protein. The new polymorphisms of the ovine CSN1S2 found in this paper are potential molecular markers that could be used to investigate its association with production traits.